'Strong enterprise, weak government': energy policy making in China. (30th June 2008) - Xu, Yi-chong
China lacks a cohesive energy plan, but in light of its rapidly increasing energy consumption and low energy efficiency, it desperately needs one. Many different actors influence energy policy, with varying degrees of impact, as the methods of policy formulation are extremely ambiguous and fluid. Chinese energy policy has been characterised by bureaucratic overlap and competition, while free market mechanisms have recently gained prominence. Currently, state-owned energy oligopolies are the key actors, but special interest groups, such as consumers, have emerged as important voices in policy formulation.